Later-Life Learning and Older Women Learners: A Feminist Commentary - Marvin Formosa (Gender a Výzkum)
Later-life learning continues to remain well under the radar as far as feminist theorising and empirical research are concerned. This exclusion is surprising considering that older women make up the majority of learners in later-life learning programmes. This essay has three objectives: to present the available knowledge on older women and learning given that this information remains undocumented; to apply a feminist critique to the mainstream literature on older adult learning, with a special reference to the University of the Third Age (U3A) and Women's Institutes (WI); and to promote an understanding of the similarities and diversities of older women by highlighting the significance of socially diverse factors such as class, ethnicity, and age in shaping their learning experiences or lack thereof. In an ageing society, organisations such as U3As and WIs have the potential to improve the quality of life of older women and the overall community in which they live. However, their role in enabling older women to attain some level of critical consciousness by leading them to reflect on everyday realities and analyse the relationships between personal contexts and the wider social forces of marginalisation was found to be marginal at best.